Study on one—dimensional consolidation of saturated soil with semi—pervious boundaries and under cyclic loading - 梁旭 蔡袁强 等 (Journal of Zhejiang University. Science, 2002)
The variation opf effective stress ratio of stratfied soil with semi-pervious boundaries and under cylic loading was analyzed on the basis of Terzaghi's one-dimensional consolidation assumptions.A solution by Laplace Transform was obtained for the case whe the soil was under time-varied loading.With numerical in version of Laplace Tranform.Some useful results were obtained for several kinds of commonly encountered loadings.The results can be meaningful in engineering preactice.